Determinants of the Financial Performance of Indonesian Islamic Banks (BSI) Kcp Kampung Tax - Mutiara Sari; Sugianto Sugianto (Penerbit Jurnal Indonesia, 2022)
This study aims to determine whether customers are able to work together in generating finances at KCP Kampung Bank Syariah Indonesia taxes. Financial performance is an analytical step to determine the extent to which the company has complied and implemented regulations regarding financial implementation properly and correctly. Islamic banks that carry out financing must be based on sharia principles which have now been mutually agreed upon. In Indonesian Sharia Commercial Banks, what is applied to customers is a profit- sharing system that does not harm the bank or its customers. Income in the world of banking, both sharia and conventional, is a proportional profit sharing between banks and customers at Bank Syariah Indonesia. The sample in this study was 108 customers of Indonesian Islamic Commercial Banks, using purposive sampling technique with certain criteria to take a sample of customers at Indonesian Islamic Commercial Banks to be studied. The analytical method used is panel data regression and data secondary.